Meta-Analysis Predictors of Sufficient Pain Management among Children at Pre-hospital Medical Service - Arief Wahyudi Jadmiko; Sang Ayu Made Adyani (Masters Program in Public Health, Sebelas Maret University, 2022)
Background: Safely treating pain in children is a critical but challenging task for emergency medical teams. Few studies have focused on pain management guidelines at the hospital or department level. This study aimed to examine predictors of good pain management in children in prehospital health services.Subject and Method: This research is a systematic review and meta-analysis study using PRISMA diagrams. The article search was conducted based on the PICO Model eligibility criteria. P: children with pre-hospital acute Pain. I: analgesic administration and male. C: no analgesic administration, and female. O: pain reduction. The articles used were from 5 databases: EBSCO, Pubmed, ProQuest, Scopus, and Science Direct. The search keywords for articles were as follows “pain management” OR “pain reduction” AND “predictors” AND “pre-hospital care” AND “children”. The inclusion criteria in this study include full-text articles with observational study designs, full-text available articles, the relationship size used is the adjusted Odds Ratio, articles published in the 2010-2022 range, and the research outcome is sufficient pain management or efficient pain reduction. Articles were analyzed using the Review Manager 5.3 application.Results: There are 8 articles in this study, 2 from Australia, 1 from the United States, 1 from Switzerland, and 4 articles from the United Kingdom. The article was analyzed using the PRISMA flow diagram. The study results show that analgesic administration has increased the odds of 3.36 times greater for pain reduction than without analgesic administration. This result was statistically significant (aOR= 3.36; 95% CI = 1.94 to 5.82; p<0.001). However, no significant results from the gender that showed there is no different between male and female patients for pain reduction (aOR= 1.12; 95% CI= 0.98 to 1.27; p= 0.100).Conclusion: Analgesic administration is sufficient pain management for children with acute Pain in pre-hospital medical care.Keywords: children, pre-hospital care, pain management, predictorsCorrespondence: Arief Wahyudi Jadmiko. Nursing Department, Faculty of Health, Universitas Pembangunan Nasional Veteran Jakarta. Jl. Raya Limo Depok 16515 West Java, Indonesia. Email: ariefwjadmiko@gmail.com. Mobile: 085647213628.Indonesian Journal of Medicine (2022), 07(04): 360-370https://doi.org/10.26911/theijmed.2022.07.04.01